Peran Mediasi Kepuasan Terhadap Loyalitas Pasien Rawat Jalan Ditinjau dari Service Quality dan Brand Trust pada Poliklinik Rumah Sakit Indriati Solo Baru - Pratiwi, Nuurannisa; Sarsono, Sarsono; Hendra, Kartika (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Research objectives, analyzing the influence of service quality and brand trust on patient loyalty mediated by satisfaction. Indriati Solo Baru Hospital Polyclinic was used as an object involving 80 outpatients as samples with a purposive sampling technique with the criteria of having visited at least 3 times. Data from all constructs were collected through questionnaires and data analysis techniques using path analysis. The conclusion after statistical testing proved the existence of a positive link between service quality and brand trust on patient satisfaction, then brand trust and satisfaction also influenced loyalty but service quality was not significant. Mediation testing proved that satisfaction played a role as a mediator in the influence of service quality on loyalty, but the role failed for brand trust